Prognostic Significance of Nuclear Factor Kappa B Expression in Locally Advanced Cervical Cancer Patients Treated Definitively With Concurrent Chemoradiation. (January 2020) - Altoos, Basel; Small, Christina; Dalal, Prarthana; Attieh, Darlene; El Achy, Samar; Parimi, Vamsi; Wei, Jian-Jun; Helenowski, Irene; Donnelly, Eric D.; Strauss, Jonathan; Small, William; Refaat, Tamer
Abstract : Objectives: Nuclear factor kappa B (NFkB) is a transcription factor shown to confer treatment resistance in tumors. A previous report suggested an association between pretreatment NFkB and poorer outcomes for cervical cancer patients treated with chemoradiation therapy (CRT). We aimed to validate their findings in a larger patient cohort. Materials and Methods: This Institutional Review Board approved study included patients with locally advanced cervical cancer patients treated with CRT. Evaluation of both nuclear and cytoplasmic immunoreactivity for NFkB was scored semiquantitatively by 3 pathologists. Cytoplasmic positivity incorporated both the intensity and percentage of immunoreactivity in invasive carcinoma ( H -score), whereas nuclear positivity was assessed by percentage of positive cells. Outcomes were stratified by NFkB overexpression and tumor characteristics. Overall survival (OS), progression-free survival (PFS), distant metastases-free survival (DMFS), and local regional control (LC) were obtained using Kaplan-Meier and differences between groups were evaluated by the log-rank test. Hazard ratios were obtained using Cox regression for both univariate and multivariate analyses. Results: The mean age was 51 years old and most (78.57%) had locally advanced disease. Five-year OS, PFS, LC, and DMFS in the entire cohort were 57.18% (confidence interval [CI], 34.06%-74.82%), 48.07% (CI, 25.50%-67.52%), 72.11% (CI, 49.96%-85.73%), and 62.85% (CI, 36.33%-80.82%), respectively. There was no significant association between NFkB expression ( H -index ≥180) and 3-year and 5-year OS ( P -value=0.34), PFS ( P -value=0.21), LC ( P -value=0.86), or DMFS ( P -value=0.18). Conclusions: Our study demonstrated that cytoplasmic NFkB-p65 expression ( H -index ≥180) was associated with a nonstatistically significant trend toward poor clinical outcomes in locally advanced cervical cancer patients treated definitively with CRT.